2017
DOI: 10.3390/w9020111
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological Modeling of Highly Glacierized Basins (Andes, Alps, and Central Asia)

Abstract: Abstract:The Soil and Water Assessment Tool (SWAT) was used to simulate five glacierized river basins that are global in coverage and vary in climate. The river basins included the Narayani (Nepal), Vakhsh (Central Asia), Rhone (Switzerland), Mendoza (Central Andes, Argentina), and Central Dry Andes (Chile), with a total area of 85,000 km 2 . A modified SWAT snow algorithm was applied in order to consider spatial variation of associated snowmelt/accumulation by elevation band across each subbasin. In previous … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Fontaine et al [29], Kang et al [31] and Galvan et al [41] determined precipitation lapse rate using the local climate station over their study areas. The majority of the previous studies estimated precipitation lapse rate within their calibration procedure [26,29,[33][34][35][36][37][38][39]. The present study demonstrated how CFSR data can be useful to improve hydrological simulation in data-scarce mountainous regions.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Fontaine et al [29], Kang et al [31] and Galvan et al [41] determined precipitation lapse rate using the local climate station over their study areas. The majority of the previous studies estimated precipitation lapse rate within their calibration procedure [26,29,[33][34][35][36][37][38][39]. The present study demonstrated how CFSR data can be useful to improve hydrological simulation in data-scarce mountainous regions.…”
Section: Discussionmentioning
confidence: 65%
“…In the case of scarce meteorological data, the determination of these parameters might become difficult [28]. In order to determine the lapse rates, most of the studies using the elevation band approach defined lapse rates as calibration parameters [27,30,[34][35][36][37][38][39][40], whereas several other studies estimated precipitation lapse rate by using local climate observations [29,31,41]. In addition, two different studies conducted by of 20 Zhang et al [28] and Zhang et al [33] in the Yellow River Basin, China, used the precipitation lapse rate given by Fontaine et al [29] for the Upper Wind River Basin, Wyoming in the USA.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the definition of elevation bands within the model subbasins can significantly improve the performance of the model in watersheds in high altitudes and large elevation gradients. With the improved snow melting algorithm (Fontaine et al, 2002), the stream flow of alpine regions could be successfully simulated by SWAT (Rahman et al, 2013;Omani et al, 2017;Grusson et al, 2015).…”
Section: Swat Modelmentioning
confidence: 99%
“…SWAT has been widely used in many studies for the simulation of runoff and nutrient cycling in agricultural and forested sites. Although there is an increasing interest in applying SWAT on snow-dominated (Grusson et al, 2015) and glacierized watersheds (Rahman et al, 2013;Garee et al, 2017;Omani et al, 2017), its transferability at spatial and temporal scales under the extreme conditions of these highaltitude environments has not been tested yet. In this study, we have a quite unique situation of a small well-gauged watershed, the Damma glacier watershed, which is part of the larger catchment feeding the Göscheneralpsee reservoir, for which we have hydrological data thanks to its use by the hydroelectric power plant.…”
Section: Introductionmentioning
confidence: 99%